The role of Galectin-1 and Galectin-3 in the mucosal immune response to Citrobacter rodentium infection - Curciarello, Renata (2014)
Despite their abundance at gastrointestinal sites, little is known about the role of galectins in gut immune responses. We have therefore investigated the Citrobacter rodentium model of colonic infection and inflammation in Galectin-1 or Galectin- 3 null mice. Gal-3 null mice showed a slight delay in colonisation after inoculation with C. rodentium and a slight delay in resolution of infection, associated with delayed T cell, macrophage and dendritic cell infiltration into the gut mucosa. However, Gal-1 null mice also demonstrated reduced T cell and macrophage responses to infection. Despite the reduced T cell and macrophage response in Gal-1 null mice, there was no effect on C. rodentium infection kinetics and pathology. Overall, Gal-1 and Gal-3 play only a minor role in immunity to a gut bacterial pathogen.